THE IMPACT OF LIQUIDITY, PROFITABILITY, AND LEVERAGE ON FIRM VALUE WITH DIVIDEND POLICY AS MODERATING VARIABLE - Stefanie, Stefanie; Yanti , Yanti (International Journal of Application on Economics and Business, 2023)
This research has the purpose to determine the impact of liquidity, profitability, and leverage on firm value, with dividend policy as the moderating variable. The secondary data from the manufacturing company such as financial statements and annual reports listed on IDX from 2017 – 2019 are used for this research. Research method using moderated regression analysis, which is tested using E-views. This study uses fixed effect model in testing hypothesis. Samples are chosen based on purposive sampling method. From 2017 to 2019, 42 manufacturers are listed on IDX, with a total of 126 dates selected as samples. This study found that liquidity and leverage have the negative and insignificant impacts on firm value, profitability has positive and significant impact on firm value, dividend policy is not able to moderate impact of liquidity and leverage on firm value, and dividend policy is able to weaken the impact of profitability on firm value.